Kajian Proses Islamisasi di Indonesia (Studi Pustaka) - Dalimunthe, Dalimunthe (Jurnal Studi Agama dan Masyarakat, 2016)
The purpose of this study to describe the entry of Islam to Indonesia and the process of Islamization in Indonesia. The results show that, A). There are three theories about the coming of Islam to Indonesia: 1) The theory of Gujarat by Snouck, said the entry of Islam comes from Gujarat, based on: a) the lack of facts that explain the role of Arabs in spreading Islam to the archipelago. b) Indonesia-India trade relations have been established long time ago. c) The oldest inscription of Islam in Sumatra illustrate the relationship between Sumatra with Gujarat. 2) Theory of Makkah, Hamka declare the entry of Islam to Indonesia first century H / 7 M, 3) The theory of its review to the Persian culture among Indonesian Islamic community have similarities with the Persians, among others: a) the 10th anniversary of Ashura Muharram or as a memorial day for the deaths of Shiite martyrdom of Husain. b) their clear affinity between Shaikh Siti jenar with Iranian Sufi Al-Hallaj. c) use of the term Iranian language in Arabic letters spelling system. d) a headstone on the grave Malikus Saleh (1297) and the tomb of Malik Ibrahim (1419) in Gresik booked from Gujarat.